Bioproducts in the growth and yield of Phaseolus vulgaris L. var. Delicia 364 - Tamayo-Aguilar, Yonger; Juarez-Lopez, Porfirio; Capdevila-Bueno, Wendy; Lescaille-Acosta, José; Terry-Alfonso, Elein (REVISTA TERRA LATINOAMERICANA, 2020)
Current food production systems require the use of alternatives with ecological and affordable approaches, among which the use of bioproducts generated by the action of microorganisms that act on plant nutrition, growth and development stands out. The objective of this work was to evaluate the response of Phaseolus vulgaris L. var. Delicia 364 to the application of bioproducts (arbuscular mycorrhizal fungi and Spiruvins) in plastic pots with a volume of 44 L capacity. The bioproduct Azofert was used in this experiment. The experiment was conducted in the municipality of El Salvador, Guantanamo province, Cuba. The treatments were distributed in a completely randomized design: (T1) Azofert without AMF (control group); (T2) Azofert without AMF + 2 L ha-1 of Spiruvins; (T3) Azofert + Rhizophagus irregularis; (T4) Azofert + Glomus cubense; (T5) Azofert + Funneliformis mosseae; (T6) Azofert + Rhizophagus irregularis + 2 L ha-1 of Spiruvins; (T7) Azofert + Glomus cubense + 2 L ha-1 of Spiruvins; (T8) Azofert + Funneliformis mosseae + 2 L ha-1 of Spiruvins. Plant height, stem diameter, number of pods, number of grains per pod, weight of 100 grains and yield were evaluated. In addition, mycorrhizal functioning was evaluated by mycorrhizal colonization and visual density. The results obtained showed that the application of bioproducts (arbuscular mycorrhizal fungi and Spiruvins) increased the growth and yield of the bean crop var. Delicia 364; in addition, with the combination Azofert + Rhizophagus irregularis + Spiruvins the highest yield was obtained with 2.11 Mg ha-1, which represents 37.9% more than the national average.